Towards Greening the Higher Education Curricular for Sustainable Development: The Zimbabwe Context - Joseph Hlongwane; Doris Chasokela (Journal of Education for Sustainable Development Studies, 2025)
Planet Earth is grappling with the pangs of climate change and natural disasters across the globe. Humanity has to keep pace with the ever-changing socio-economic and natural challenges and plan for a sustainable future. Environment conservation is paramount for sustainability. It is against this backdrop that this study was carried out. The main thrust was to develop sustainable strategies to be employed by Higher Education Institutions (HEIs) in a bid to spearhead environment conservation and natural disaster risk management in communities for a more sustainable future. HEIs can leverage their academic muscles and modern technological tools like Artificial Intelligence (AI) and the Internet of Things (IoT) to green their curricula, pedagogies, and assessment mechanisms to produce conservation astute graduates who can generate practical knowledge-driven solutions to societal problems and generate socio-economic empowerment from the natural resources abound in Zimbabwe, leveraging on the Heritage based Education system anchored on Education 5.0 which emphasizes industrialization and innovation. The study employed the Hermeneutic Phenomenology design situated in the interpretivist paradigm and used systematic literature review, and document analysis to collect data which was thematically analysed to design a framework for greening the curricula across different learning disciplines, especially those not directly linked to environmental issues. The study also envisaged a holistic approach incorporating various stakeholders within and without education circles. Conclusions drawn include the prospect of making HEIs vehicles for change and awareness creation by effecting the curriculum development strategies suggested. Recommendations include explicitly including environmental issues in all curricula, and engaging in multi-sectoral collaboration among curriculum designers, policymakers, examination bodies, and community personnel. The second part of the research focussed on presenting a framework that STEM educators can use to green their modules. The researchers argue that if every module is green then the whole curriculum would be green.